2007
DOI: 10.1149/1.2776128
|View full text |Cite
|
Sign up to set email alerts
|

Toward Real-Time Simulation of Physics Based Lithium-Ion Battery Models

Abstract: Recent interest in lithium-ion batteries for electric and hybrid vehicles, satellite, defense, and military applications has increased the demand on the computational efficiency of lithium-ion battery models. This paper presents an effective approach to simulate physics based lithium-ion battery models in real-time ͑milliseconds͒ for simulation and control in hybrid environments. The battery model used for the simulation is derived from the first principles as an isothermal pseudo two-dimensional model with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 18 publications
1
98
0
Order By: Relevance
“…Consequently, several simplifications of their model have been published to reduce the computation time associated with diffusion of lithium ions in the solid phase. [8][9][10] Also, Subramanian et al 11 developed a real-time simulation model using a combination of perturbation techniques, volume averaging, and intuition-based simplications. Although they reported that the computational time for their real-time simulation model for a single process was around 100 ms, to derive the lower-order model by using this method one needs to carry out preprocessing and have a priori knowledge of the behavior of the system under different conditions, which makes their method less flexible than desired.…”
mentioning
confidence: 99%
“…Consequently, several simplifications of their model have been published to reduce the computation time associated with diffusion of lithium ions in the solid phase. [8][9][10] Also, Subramanian et al 11 developed a real-time simulation model using a combination of perturbation techniques, volume averaging, and intuition-based simplications. Although they reported that the computational time for their real-time simulation model for a single process was around 100 ms, to derive the lower-order model by using this method one needs to carry out preprocessing and have a priori knowledge of the behavior of the system under different conditions, which makes their method less flexible than desired.…”
mentioning
confidence: 99%
“…Safety concerns include safeguarding against fire, explosion, and the corrosive nature of the electrolyte, as well as the venting of toxic or flammable gases [48,85,[88][89][90][91][92][93][94][95][96][97][98]. All auxiliary equipment such as thermal sensors, thermostats, heaters and switching devices must be designed so that they cannot be the source of an explosion.…”
Section: Safetymentioning
confidence: 99%
“…These models are usually solved by using only a single numerical treatment, e.g., Runge-Kutta, Newton or Crank-Nicholson methods. Subramanian et al [14] developed a method to reduce the number of the governing equations of Li-ion battery simulation by using different mathematical techniques. The original problem with a proper discretization consists of 4800 equations which can be reduced to 49, and finally the simulation time of the discharge curve can be cut to 85 ms.…”
Section: Applicationmentioning
confidence: 99%